Bactéries d’origine alimentaire résistantes aux antibiotiques: détection, isolement et formation de biofilms. - AZZAOUI, Asmae; BELHAKEM Selma, Khadidja (My University, 2020)
During this work, a rapid protocol was established in order to detect and isolate bacteria with antibiotics resistance contained in some dairy products. This resistance was tested against 7 antibiotics: fusidic acid, chloramphenicol, erythromycin, oxacillin, penicillin G, spiramycin and vancomycin, on TSA and MRS agar, using agar diffusion method. The observed results vary both according to the medium used and the nature of the product analysed. For example, the isolates from industrial butter showed susceptibility to the majority of the antibiotics tested on the two media used. All the preselected antibiotic-resistant isolates were pre-identified by the determination of their morphological aspects (macroscopic and microscopic). Finally, for some selected isolates, an antibiogram was performed to confirm and verify the effectiveness of the protocol followed. The isolates İ3 (traditional butter), İ7 (traditional butter) and İ8 (industrial butter) detected respectively resistant to spiramycin, fusidic acid and vancomycin, showed after confirmation a multi-resistance to the tested antibiotics. Furthermore, the scientific papers of Lin et al. (2019) and Karapetkov et al. (2011), translated and presented rather than analysed, reported and confirmed the occurrence of antibiotic-resistant bacteria in several types of food products, including ready-to-eat foods, dairy products and fruits.
Keywords: antibiotic-resistant bacteria; occurrence; foods; dairy products; antibiotics; detection; isolation; biofilm formation.